Investigating L2 spoken English through the role play learner corpus - Nava, Andrea; Pedrazzini, Luciana (Studies in Second Language Learning and Teaching, 2011)
We describe an exploratory study carried out within the University of Milan, Department of English the aim of which was to analyse features of the spoken English of first-year Modern Languages undergraduates. We compiled a learner corpus, the “Role Play” corpus, which consisted of 69 role-play interactions in English carried out by first-year students at B1+-B2 levels according to the Common European Framework of Reference. The analysis focused on the students’ use of two features of spoken English grammar, tails and the discourse markers ‘yes’ and ‘yeah’. Instances of these features from the data were compared with examples of British native speaker, learner and Italian native speaker usage. Preliminary findings pointed to the role of the students’ first language, L2 proficiency and specific task features in the range and frequency of these phenomena as well as in the functions they deployed in the spoken discourse of the informants.